Phantasms of Computability. (3rd July 2016) - Rautzenberg, Markus
Abstract : Computer games are messy entanglements of computers and games. This correlation results in a specific tension between a medium (the computer) that is dependent on computability (meaning first and foremostdecidability ) and a medium (play and game) that is decisivelynot . The article is based on the observation that there is really not much that has changed since the groundbreaking analyses of Max Weber and Emile Durkheim concerning the inner state of mind of capitalism; we are still living in a world where uncertainty is a state or a mode of existence that we have to cope with. Computer Games are ways of 'coping' or 'dealing' with this uncertainty by staging it over and over again, a capability that is mirrored and amplified by the computer, whose greatest achievement in the history of media is reversibility, something that is otherwise completely unattainable in our everyday life. So in a way in computer games we can observe the computer 'dreaming', staging as phantasms what it is dependent upon.